2022
DOI: 10.20996/1819-6446-2022-06-04
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Enhanced External Counterpulsation on the Vascular State, Indicators of Glycemic Control and Quality of Life in Patients with Coronary Artery Disease and Type 2 Diabetes Mellitus

Abstract: Aim. To study the effect of enhanced external counterpulsation (EECP) on the functional status, quality of life, structural and functional state of the vascular bed, and markers of glycemic control in patients with coronary artery disease (CAD) and type 2 diabetes mellitus (DM).Material and methods. A pilot prospective randomized study included 30 patients with CAD and DM. Using a random number generator, patients were randomized into 2 groups: EECP (n=15) and a comparison group (n=15). All patients (n=30) rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Simultaneously, along with the improvement in the microcirculation, an increase in the number and density of muscle capillaries, enhancement of the metabolic capacity and ability of the exercise muscle groups to use oxygen, improvements in the exercise endurance of patients, and reduced fatigue were observed [13,55] . Slepova et al [54] evaluated the efficacy of EECP in the treatment of patients with CAD and type 2 diabetes mellitus using data from the 6-minute walking distance, dynamic ECG, and left ventricular ejection fraction, and concluded that compared to conventional treatment, the administration of EECP can significantly improve the symptoms of angina pectoris, reduce the www.cardiologyplus.org He XF et al: Cardiology Plus time of myocardial ischemia, and improve the control of blood sugar and exercise tolerance. After EECP treatment, the exercise tolerance time of RAP patients increased from 6.48 to 9.20 minutes and the left ventricular ejection fraction increased from 42.65% to 44.26% [56] .…”
Section: Increasing the Exercise Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneously, along with the improvement in the microcirculation, an increase in the number and density of muscle capillaries, enhancement of the metabolic capacity and ability of the exercise muscle groups to use oxygen, improvements in the exercise endurance of patients, and reduced fatigue were observed [13,55] . Slepova et al [54] evaluated the efficacy of EECP in the treatment of patients with CAD and type 2 diabetes mellitus using data from the 6-minute walking distance, dynamic ECG, and left ventricular ejection fraction, and concluded that compared to conventional treatment, the administration of EECP can significantly improve the symptoms of angina pectoris, reduce the www.cardiologyplus.org He XF et al: Cardiology Plus time of myocardial ischemia, and improve the control of blood sugar and exercise tolerance. After EECP treatment, the exercise tolerance time of RAP patients increased from 6.48 to 9.20 minutes and the left ventricular ejection fraction increased from 42.65% to 44.26% [56] .…”
Section: Increasing the Exercise Capacitymentioning
confidence: 99%
“…Slepova et al . [54] evaluated the efficacy of EECP in the treatment of patients with CAD and type 2 diabetes mellitus using data from the 6-minute walking distance, dynamic ECG, and left ventricular ejection fraction, and concluded that compared to conventional treatment, the administration of EECP can significantly improve the symptoms of angina pectoris, reduce the time of myocardial ischemia, and improve the control of blood sugar and exercise tolerance. After EECP treatment, the exercise tolerance time of RAP patients increased from 6.48 to 9.20 minutes and the left ventricular ejection fraction increased from 42.65% to 44.26% [56] .…”
Section: Application Of Eecp In Cardiac Rehabilitation Of Chdmentioning
confidence: 99%
See 1 more Smart Citation